Medical Rehabilitation in Patient with Cerebral Palsy Spastic Diplegic GMFCS IV MACS I CFCS IV EDACS II - Rondonuwu, Gloria; Gessal, Joudy; Angelina, Chelsy (e-CliniC, 2024)
Abstract: Children with cerebral palsy are present with three types of motor problems. The major disturbances in muscle tone, balance, strength, and selectivity are directly related to damage of the central nervous system. Treatment programs encompass physical and behavioral therapy, pharmacologic and surgical treatments, mechanical aids, and management of associated medical conditions. In physical, occupational, speech, and behavioral therapies, the goals include enhancing patient and caregiver interactions while providing family support. We reported a female, 7-year-old, with cerebral palsy spastic diplegic GMFCS IV MACS I CFCS IV EDACS II. The patient was treated with USD intensity 1 watt/cm2, frequency 3.3 MHz in 5 minutes and continuous stretching in four extremity for 10 minutes each. It showed improvement from the popliteal angle assessment and MAS score, therefore, additional invasive therapy, such as botox injection, might be not needed in the meantime. Stiffness in lower extremities especially at gastrocnemius muscle was treated with ESWT energy of 0.15mJ/mm2; total shots dose 1500 shocks per each treated muscle (gastrocnemius); frequency 4 Hz. The patient presented with lumbar hyperlordotic and anterior pelvic tilt, and also tended to sway posteriorly during standing and walking, resulting poor protection reaction on the anterior side. It will be beneficial to add abdominal core and hip extensor strengthening exercise into the program. For walking aids, we considered about using anterior walker or posterior walker. However, since the patient was 4 years old and could not take complex instruction, it might become challenging to modify the exercise protocol. Regular daily stretching was beneficial for the home program and should be continued. Referral to surgery was not required at this moment due to no joint contracture. Keywords: cerebral palsy; motor problem; gait rehabilitation